1974
DOI: 10.1111/j.1476-5381.1974.tb08586.x
|View full text |Cite
|
Sign up to set email alerts
|

ATROPINE‐RESISTANT EFFECTS OF THE MUSCARINIC AGONISTS McN‐A‐343 AND AHR 602 ON CARDIAC PERFORMANCE AND THE RELEASE OF NORADRENALINE FROM SYMPATHETIC NERVES OF THE PERFUSED RABBIT HEART

Abstract: 1 The effects of 4-(m-chlorophenylcarbamoyloxy)-2-butynyltrimethylammonium chloride and N-benzyl-3-pyrrolidyl 4 McN-A-343, cocaine and desipramine (but not AHR 602 or hexamethonium) blocked the net cardiac noradrenaline uptake and increased the positive chronotropic effect of noradrenaline. 5 Prior perfusion with concentrations of cocaine and desipramine sufficient to block uptake reduced or abolished the facilitatory effects of both McN-A-343 and AHR 602 on SNS. 6 Cocaine, McN-A-343 and AHR 602 displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…One possible explanation for the effect of AHR-602 is the local anaesthetic action observed with high concentrations of the agonist (Fozard & Muscholl, 1974). The failure of AHR-602 to activate muscarinic receptors in the ear artery was in agreement with findings for prejunctional muscarinic receptors on sympathetic nerves in the rabbit heart (Fozard & Muscholl, 1972) but was unexpected given that McN-A-343 was an agonist in the ear artery.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…One possible explanation for the effect of AHR-602 is the local anaesthetic action observed with high concentrations of the agonist (Fozard & Muscholl, 1974). The failure of AHR-602 to activate muscarinic receptors in the ear artery was in agreement with findings for prejunctional muscarinic receptors on sympathetic nerves in the rabbit heart (Fozard & Muscholl, 1972) but was unexpected given that McN-A-343 was an agonist in the ear artery.…”
Section: Discussionsupporting
confidence: 71%
“…AHR-602 produced some inhibition ofresponses to stimulation of the rabbit ear artery, but this was not exerted via activation of the prejunctional muscarinic receptor as the inhibition was unaffected by atropine in concentrations up to 100 nM. One possible explanation for the effect of AHR-602 is the local anaesthetic action observed with high concentrations of the agonist (Fozard & Muscholl, 1974). The failure of AHR-602 to activate muscarinic receptors in the ear artery was in agreement with findings for prejunctional muscarinic receptors on sympathetic nerves in the rabbit heart (Fozard & Muscholl, 1972) but was unexpected given that McN-A-343 was an agonist in the ear artery.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be more appropriate to compare the stimulation-evoked 'H-overflow with the area under the time-tension curve. It has been suggested that McN-A-343 increased the release of NA from sympathetic nerves as a result of inhibition of transmitter re-uptake (Allen et al 1972;Fozard & Muscholl 1974;Nedergaard 1980a). Thus McN-A-343 inhibits the accumulation of 'H-NA by guinea-pig atria (Allen er af.…”
Section: Discussionmentioning
confidence: 99%
“…Thus McN-A-343 inhibits the accumulation of 'H-NA by guinea-pig atria (Allen er af. 1972), perfused rabbit heart (Fozard & Muscholl 1974) and rabbit aorta (Nedergaard 1980a). Evidence has been presented for the view that cocaine potentiates the contractile response of sympathetically innervated organs elicited by exogenous NA by inhibiting the uptake-I mechanism (Trendelenburg 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation